Dichotomous "Good Outcome" Indicates Mobility More Than Cognitive or Social Quality of Life. Issue 8 (August 2015) - Naidech, Andrew M.; Beaumont, Jennifer L.; Berman, Michael; Francis, Brandon; Liotta, Eric; Maas, Matthew B.; Prabhakaran, Shyam; Holl, Jane; Cella, David
<x xml:space="preserve">Abstract</x> Objective: Worthwhile interventions for intracerebral hemorrhage or subarachnoid hemorrhage generally hinge on whether they improve the odds of good outcome. Although good outcome is correlated with mobility, correlations with other domains of health-related quality of life, such as cognitive function and social functioning, are not well described. We tested the hypothesis that good outcome is more closely associated with mobility than other domains. Design: We defined "good outcome" as 0 through 3 (independent ambulation or better) versus 4 through 5 (dependent) on the modified Rankin Scale at 1, 3, and 12 months. We simultaneously assessed the modified Rankin Scale and health-related quality of life using web-based computer adaptive testing in the domains of mobility, cognitive function (executive function and general concerns), and satisfaction with social roles and activities. We compared the area under the curve between different health-related quality of life domains. Setting: Neurologic ICU with web-based follow-up. Patients: One hundred fourteen patients with subarachnoid hemorrhage or intracerebral hemorrhage. Interventions: None. Measurement and Main Results: We longitudinally followed 114 survivors with data at 1 month, 62 patients at 3 months, and 58 patients at 12 months. At 1 month, area under the curve was highest for mobility (0.957; 95% CI, 0.904–0.98), higher than cognitive function–general concerns (0.819; 95% CI, 0.715–0.888; p = 0.003 compared with mobility), satisfaction with social roles and activities (0.85; 95% CI, 0.753–0.911; p = 0.01 compared with mobility), and cognitive function–executive function (0.879; 95% CI, 0.782–0.935; p = 0.058 compared with mobility). Optimal specificity and sensitivity for receiver operating characteristic analysis were approximately 1.5 SD below the U.S. population mean. Conclusions: Health-related quality of life assessments reliably distinguished between good and poor outcomes as determined by the modified Rankin Scale. Good outcome indicated health-related quality of life about 1.5 SD below the U.S. population mean. Associations were weaker for cognitive function and social function than mobility.